The Effect Of A Cognitive Behavioral Therapy Program On The Depression Among Abused Adolescents - Kittimaskun, Wallapa; Bunthumporn, Nutchanart; Vuthiarpa, Sararud (Journal of The Royal Thai Army Nurses, 2020)
This quasi-experimental research to study the effect of a cognitive behavior therapy program on depression among abused adolescents. The sample group included the abused adolescents who reside at children’s shelters in the central region, aged 15-18 years old; one boy and one girl are selected by simple random sampling from each shelter as the experimental group who received the cognitive behavior therapy program and as the control group who receive normal treatment at 7 shelters. The qualifications of the samples resulted in 30 samples for each group. The tools for this research were 1) the depression evaluation 9Q, 2) the questionnaire asking personal information, experience, and duration of being abused, 3) the cognitive behavior therapy program, and 4) the center for epidemiological studies-depression scale (CES-D) Thai version. The cognitive behavior therapy program had been verified its content, accuracy, clearness, and appropriateness by 3 experts. The depression evaluation 9Q and CES-D Thai version have Cronbach’s Alpha Coefficient at .82 and .86. Data analysis was processed with descriptive statistics, Dependent T-test and Independent T-test. According to the result, it was found the mean of depression of the experimental group after attending the program is lower than before the experiment with statistical significance (p<.001) and the depression means before and after the program between the experimental group and the control group are different with statistical significance (p<.001), which represents that the program has the effect to decrease depression for abused adolescents.